Thoroughbred [videorecording (DVD)] : born to run - Wagner, Paul, 1948-; Walker, Kathryn, 1943- (PBS Home Video, 2011)
Follows a group of individuals and horses for a year leading up to the 2009 Kentucky Derby, and captures the beauty of the breed, the thrilling nature of the sport, and the deep reservoir of history and tradition behind this equine wonder. Viewers go from Kentucky to Dubai to trace the breed's fascinating history and meet the people who breed them, sell them, race them, and love them. From foaling barn to finish line this unique animal imbues the story of the thoroughbred with power and meaning.